Անցյալի հիշողությունը կամ պատմությունը՝ որպես ակտիվ քաղաքական գործոն. այսօրվանից մինչև Մովսես Խորենացի - Սարգսյան, Աշոտ («Նաիրի» հրատ.)
A nation’s self-concept influences its political conduct and is manifested in three ways: 1) Over self-estimation, when seeming heroism can be unreasonably exaggerated, turn into maleficent adventurism, and lead to nonrecoverable losses. 2) Under self-estimation, when extreme caution may lead to indifference, maleficent inertness, and negligence of historically given chances. 3) Objective self-estimation, when a nation’s mentality becomes rational, its conduct and actions correspond to its abilities, are adequate to the reality and eo ipso are most effective. A nation’s own history forms the main, if not the only, basis of its self-estimation. Together with other factors, it forms the mentality and political conceptions of that nation and its political elite, influencing its plans and conduct. Already in the 5th century, the Father of History Movses Khorenatsi was profoundly aware of this eternal political problem and solved it in favour of a third possibility. In the light of this consciousness he - Regarded the creation of a written history of his people extremely important; he speaks about this at length for several times. - Took on the important task of neither embellishing nor disparaging the past but of striving for maximal objectiveness and truthfulness. - Rejected any fantastic elements in the narrative and the widespread practice of explaining this or that event by “the providence from above.” - Excluded from his work, as far as possible, all inner contradictions and based himself on facts and logic. Представление нации о самой себе воздействует на ее поли- тическое поведение и может проявляться в трех вариантах: 1) Самопереоценка, при которой кажущийся героизм может непродуманно абсолютизироваться, превращается в преступный авантюризм и приводит к невосполнимым потерям. 2) Самонедооценка, при которой осторожность, доведенная до крайности, может привести к индифферентности, к преступному бездействию, при котором исторически предоставленные шансы остаются без внимания. 3) Объективная оценка, при которой мышление нации становится рациональным, а поведение соответствующим своим силам, адекватным действительности и тем самым – наиболее результативным. Основа суждения нации о себе (если не единственная, то по крайней мере главная) – собственная история. Она, в числе других факторов, образует представления и политичесую мысль нации и ее политической элиты, влияет на ее планы и образ действий. Уже в 5-ом веке Отец истории Мовсес Хоренаци глубоко сознавал эту проблему, существующую во все времена, и решал ее в пользу третьей возможности. В свете этого сознания он, в частности: - Считал исключительно важной задачей создание письменной истории народа, о чем он пространно высказывался несколько раз. - Ставил перед собой задачу ни в коей мере не приукрашивать прошлое, но и не принижать его, а стремиться к наибольшей объективности и достоверности. - Полностью отказался от фантастических элементов повествования, от распространенной практики объяснения какого-либо эпизода “провидением свыше.”
Keywords: Պատմություն; Աղբյուրագիտություն